ELAZIĞ CİP BARAJ GÖLÜ?ARINDIK KÖYÜ ARASI SAHANIN FLORASI - DOĞAN, GÜLDEN (Fırat Üniveristesi, 2009)
Bu çalışma, Elazığ Cip Baraj Gölü-Arındık Arasındaki Sahanın florasını tespit etmek amacıyla yapılmıştır. Araştırma alanından toplanan 992 bitki örneği alandan toplanmıştır. 72 familya ait 246 cins ve 378 takson (tür, alttür ve varyete) tespit edilmiştir. 2 takson Pteridophyta, 376 takson ise Spermatophyta bölümlerine aittir. Spermatophyta'ya ait taksonların 3'ü Coniferophyta, geriye kalan 373'ü Magnoliophyta alt bölümü içinde temsil edilmektedir. 373 taksonun 336'sı Magnoliopsida, 37'si ise Liliopsida sınıflarına ait olduğu bulunmuştur. Toplanan taksonların endemizm oranı % 8.62 olarak belirlenmiştir (toplam 32 takson). Çalışma alanındaki taksonların fitocoğrafik bölgelere göre dağılımı sırasıyla şöyledir; İran-Turan elementleri 123 (%32.5), Akdeniz elementleri 16 (% 4.2), ve Avrupa-Sibirya elementleri 8 (%2.1). Çalışma alanında bulunan en büyük familyalar: Fabaceae (42), Asteraceae (40), Lamiaceae (29), Brassicaceae (23), Caryophyllaceae (21), Boraginaceae (19), Poaceae (17), Apiaceae (16), Ranunculaceae (12) ve Rosaceae (12) şeklindedir. Diğer taraftan, Astragalus-Vicia-Salvia cinsleri takson sayısına göre en büyük cinslerdir.Anahtar Kelimeler: Flora, Türkiye, Elazığ, Endemik, Takson, Astragalus, Vicia, Salvia

This study was carried out to determine the flora of the area located between Elazığ Cip dam reservoir and Arındık village. 992 plant specimens were collected from the area. 246 genera and 378 taxa (species, subspecies and varities) belongs to the 72 families were determined. Two taxa are represented in Pteridophyta and 376 taxa belongs to the Spermatophyta division. 3 taxa belongs to the Coniferophyta subdivisio and the rest, 373 taxa were represented in Magnoliophyta subdivisio. 336 taxa were found as belong to the Magnoliopsida, 37 taxa belongs to the Liliopsida classes. The endemism ratio of the collected taxa were determined as 8.62 % (totally 32 taxa). The distiribution of the taxa determined in the studied area according to the phytogeographic regions were found as: Irano-Turanian elements were 123 (32,5 %); Mediterranean elements were 16 (4.2%) and Euro-Siberian elements were 8 (2.1%) respectively. The largest families in the studied area were found as following: Fabaceae (42), Asteraceae (40), Lamiaceae (29), Brassicaceae (23), Caryophyllaceae (21), Boraginaceae (19), Poaceae (17), Apiaceae (16), Ranunculaceae (12) and Rosaceae (12). On the other hand; Astragalus, Vicia and Salvia genera in the located area were found as largest genera according to taxa number.Keywords: Flora, Elazığ, Cip lake, Endemic, Astragalus, Vicia, Salvia.
The flora of the area located between Elaziğ Cip dam reservoir and Arindik village
Keywords: Botanik